Trans-Pacific Strategic Partnership: the Balance of Power and Role in the Formation of Regional Free Trade Area in Asia- Pacific - G. M. Kostyunina (Vestnik MGIMO-Universiteta)
The article describes the main provisions of existing agreement on the transpacific strategic economic partnership, the need for expansion and its importance to the future Asia-Pacific free trade area (FTAAP). It analyzes of the positions of the leading countries in the region on a Pacific free trade zone - the U.S., Japan and ASEAN.